HUBUNGAN PENGGUNAAN INTERNET TERHADAP KONSENTRASI BELAJAR - Nadila Mutiara Suci; Ari Pristiana Dewi; Ganis Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
The internet can have a negative effect to students if it is used excessively, so that it can affect on student’s academic achievement. The purpose of this research was to determine the relation between internet usage and the concentration of learning and achievements on Nursing Students at the University of Riau Faculty of Nursing. This research used a cross sectional approach with 218 samples taken using stratified random sampling techniques. The data in this research consisted of primary data was collected by questionnaires, and secondary data was obtained from the students’ Cumulative Grade Point Average (CGPA). Data analysis used chi square test. The results showed that there was a relation between the duration of internet usage and the concentration of learning on Nursing Student at the University of Riau Faculty of Nursing students with p value 0.011 <α (0.05), there was a relation between the duration of internet usage and student achievement with p value 0.011 <α (0.05 ), and there was a relation between the application used in the internet use of the Faculty of Nursing in Riau University with p value 0,000 <α (0,05), there is a relationship between the application used in internet use and learning achievement in nursing students at Riau University with p value 0,013 <α (0.05), there was a relation between the devices are used with the concentration of learning in the University of Riau Nursing Faculty students with p value 0,000 <α (0,05), and there is a relationship between the devices are used with learning achievement on Nursing Students at the University of Riau Nursing Faculty with p value 0,000 <α ( 0.05). Based on these results, researcher suggest that educational institutions have to pay more attention to the use of internet in learning activity.   Keywords:Internet Usage , Learning Achievement,  Learning Concentration